DIETARY SILICA NANOPARTICLE AMELIORATES THE GROWTH PERFORMANCE AND MUSCLE COMPOSITION OF STINGING CATFISH, HETEROPNEUSTES FOSSILIS - Partha Sarathi Das; Md Fazle Rohani; Basim. S. A. Al Sulivany; Salman Shahriar Nibir; Runa Akther Juthi; Abdus Satter; Md Sazzad Hossain; Shameeran Salman Ismael (Science Journal of University of Zakho)
Silica nanoparticles (Si-NPs) are increasingly prevalent in various industrial applications, potentially impacting aquaculture. The study investigated the effects of dietary Si-NPs on growth performance and its repercussions on muscle compositions in Stinging catfish, Heteropneustes fossilis (H. fossilis). In this study, four isonitrogenous diets containing Si-NPs (0, 1, 2, and 3 mg/kg) were fed to juvenile H. fossilis for 60 days. Several growth indices (weight gain, WG; percent weight gain, %WG; length gain, LG; and specific growth rate, SGR), feed utility parameters (feed conversion ratio, FCR; feed conversion efficiency, FCE; and protein efficiency ratio, PER) and survival rate was assessed at the end of the feeding trial. This study showed significant effects of Si-NPs (2 mg/kg) in the growth and muscle composition of H. fossilis. However, Si-NPs did not significantly affect the feed utility of H. fossilis. The findings of this study recommended that Si-NPs can be effectively supplemented into the diets of H. fossilis for better production.